2021
DOI: 10.1186/s12885-021-07885-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional risk index and postoperative one-year skeletal muscle loss can predict the prognosis of patients with gastric adenocarcinoma: a registry-based study

Abstract: Background Patients with gastric cancer have an increased nutritional risk and experience a significant skeletal muscle loss after surgery. We aimed to determine whether muscle loss during the first postoperative year and preoperative nutritional status are indicators for predicting prognosis. Methods From a gastric cancer registry, a total of 958 patients who received curative gastrectomy followed by chemotherapy for stage 2 and 3 gastric cancer a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…As an easily obtainable biological indicator, PNI has been widely considered to dynamically reflect the immune function and nutritional status of the whole body ( 19 ). Since the innovative application of PNI by Onodera T for assessing the surgical risk and prognosis of patients with gastrointestinal malignancies, numerous studies ( 20 23 ), including our work, have demonstrated that PNI could be a significant prognostic factor for evaluating both short- and long-term outcomes of GC patients. Wang et al ( 15 ) found that the fibrinogen and PNI (FPNI) score was significantly associated with advanced age, large tumor size, high American Society of Anesthesiologists (ASA) scores, late TNM stage, and poor prognosis ( P < 0.01).…”
Section: Discussionmentioning
confidence: 81%
“…As an easily obtainable biological indicator, PNI has been widely considered to dynamically reflect the immune function and nutritional status of the whole body ( 19 ). Since the innovative application of PNI by Onodera T for assessing the surgical risk and prognosis of patients with gastrointestinal malignancies, numerous studies ( 20 23 ), including our work, have demonstrated that PNI could be a significant prognostic factor for evaluating both short- and long-term outcomes of GC patients. Wang et al ( 15 ) found that the fibrinogen and PNI (FPNI) score was significantly associated with advanced age, large tumor size, high American Society of Anesthesiologists (ASA) scores, late TNM stage, and poor prognosis ( P < 0.01).…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, it evolved to a widely accepted biomarker in many cancer entities, including HCC. [10][11][12][13][14][15][16] Two meta-analyses reported on an…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it evolved to a widely accepted biomarker in many cancer entities, including HCC. 10–16 Two meta-analyses reported on an independent prognostic value of PNI in patients following hepatectomy and non-surgical treatments, whereas predictive significance in the LT setting remained undetermined. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations